Proyecto artístico y proyecto asistencial, concurrencias y congruencias - Vareilles, Christophe de (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2006)
The paper affirms that art does not recover but can be therapeutic, and suffering can be an opportunity to create instead of an obstacle to the creation. Opposite to a conception of art therapy in hospitable context as workshop of leisure or space of distraction and withdrawal of oneself, a vision of art therapy appears as learning of self, as contact with the unacceptable, asocial and darkly of the own singularity. The art therapy workshop is a place of meeting and clash with self, taking advantage of a context without risk that contributes the artistic activity, unlike other spaces socialized of the daily life.
Keywords: Art therapy; Hospital; Learning of self; Care; Singularity